Private Partnership Program (PKM) Teachers Creativity SMP YPM 4 Bohar Taman Sidoarjo Through School Magazine - Ardianik Ardianik; Farida Farida; Edy Widayat (OJS Universitas Muhammadiyah Gresik, 2019)
The partner of this community partnership program is SMP YPM 4 Bohar, located on Jl. Raya Bohar No. 39 Taman Sidoarjo as a container for the generation of the nation, always applies various methods and development of learning media to answer the demands of the times to produce high-quality human resources, the obstacle faced by this school is the ability of teachers in the field of journalism is still inadequate, in addition there is also no media learning that is able to accommodate the creativity of teachers and students. Therefore it is necessary to provide journalistic training to the teachers and learning media need to be made by publishing ISSN school magazines that are able to accommodate the creativity of teachers and students in writing papers. The benefits of making this school magazine are: (1) as acommunication medium; (2) as a medium of creativity; 3) as a medium to improve writing skills; (4) as a medium for developing reading habits; (5) as a time filler; (6) as a medium for training intelligence thinking; (7) as a medium for training in organization:; (8) as a promotional media. There are three stages in implementing a solution that must be completed with a partner: 1) Training; 2) Assignment, and 3) Assistance. The results of community service as a whole can be concluded; 1) There is a significant difference before and after the training, before and after the school magazine is made, this can be seen from the results of the paper that will be loaded in the school magazine showing that teachers and students can express a variety of ideas, various ideas, thoughts , creativity, even fantasy that accompanies thedevelopment of a student's soul through various kinds of writing so that it can be read by all other students and teachers; 2) During the process of making school magazines, partners and service teams work together so that the specified targets can be implemented well. The first school magazine with the name